Development of piperazine-1-carbothioamide chitosan silver nanoparticles (P1C-Tit*CAgNPs) as a promising anti-inflammatory candidate: a molecular docking validation. Issue 4 (4th April 2018) - Karthik, C. S.; Manukumar, H. M.; Sandeep, S.; Sudarshan, B. L.; Nagashree, S.; Mallesha, L.; Rakesh, K. P.; Sanjay, K. R.; Mallu, P.; Qin, Hua-Li
Abstract : Natural products are important leads in drug discovery. Abstract : Natural products are important leads in drug discovery. The search for effective plant-derived agents or their synthetic analogues has continued to be of interest to biologists and chemists for a long time. Herein, we have synthesized a novel compound, P1C, and P1C-Tit*CAgNPs from chitosan; P1C is a precursor and an anti-inflammatory candidate, which has been validated by molecular docking studies. The synthesized P1C-Tit*CAgNPs showed monodisperse, spherical, and cationic nature and antioxidant properties, protecting destabilization of the erythrocyte membrane by the azo compound 2, 2′-azobis(2-amidinopropane)dihydrochloride (AAPH); the involvement of NPs as a protective agent for biomolecules, such as DNA and protein, followed by the treatment of NPs with AAPH was confirmed. The inhibition of cellular damage and leakage of cellular inflammatory agents was confirmed by AFM, SEM, TEM, SDS-PAGE, LDH, and PLA2 enzyme inhibition via in vitro studies. The anti-inflammatory property of P1C was further validated by in silico molecular docking studies and showed that, the P1C best pose aligned to PLA2 compared to standard drug. The significant anticancer property of P1C-Tit*CAgNPs was confirmed against MCF7, U373, and C6 cancer cell lines. Thus, the present study highlights the synthesized P1C in P1C-Tit*CAgNPs as a target PLA2-specific anti-inflammatory candidate, and further tuning of small and development-functionalized nanoparticles has a great future in medicine; hence, their clinical applications are warranted.